Antidepressant treatment with mirtazapine, but not venlafaxine, lowers cortisol concentrations in saliva: a randomised open trial - Scharnholz, Barbara; Weber-Hamann, Bettina; Lederbogen, Florian; Schilling, Claudia; Gilles, Maria; Onken, Vera; Frankhauser, Pascal; Kopf, Daniel; Deuschle, Michael (Psychiatry research, 2010)
Lowering the concentrations of free cortisol in depressed patients may be an important prerequisite to prevent glucocorticoid-related sequelae of depression. We tested the hypothesis that the hypothalamus-pituitary-adrenal (HPA) system-dampening effects of venlafaxine and mirtazapine differ. We compared the course of morning (08.00h) and afternoon saliva cortisol (16.00h) in 42 mirtazapine- and 45 venlafaxine-treated depressed patients during a 1-week wash-out and a 4-week treatment period in a randomised open trial. Mirtazapine lowered afternoon cortisol from week 1 to 4. In contrast, during the course of the entire treatment period, venlafaxine did not attenuate saliva cortisol concentrations. Treatment effects of mirtazapine on cortisol concentrations did not differ in remitters and non-remitters to treatment. High baseline cortisol concentrations, on the other hand, were related to an unfavourable course during venlafaxine treatment and patients remitting during venlafaxine treatment had significantly lower afternoon cortisol concentrations in saliva, when compared to non-remitting patients. Thus, mirtazapine and venlafaxine show different effects on HPA system activity as measured by saliva cortisol. This may be of relevance with regard to physical sequelae of depression.
Gesehen am 31.05.2023